MENINGKATKAN PEMAHAMAN TENTANG KONSEP BUDAYA ISLAM PADA MAHASISWA PRODI PENDIDIKAN SEJARAH PADA MATA KULIAH SEJARAH KEBUDAYAAN ISLAM MELALUI PEMBELAJARAN THINK PAIRE SHARE - Muntholib, Abdul; Siregar, Insan Fahmi; Purnomo, Arif (Universitas Negeri Semarang, 2010)
Abstract. This research was aimed to increase of students understanding about Islamic culture concept. Problem of research can formulated: (1) how think pairshare models of learning can improve students understanding about Islamic culture concept?, and (2) howÃ¢â‚¬Å¸s the models got positive respon from the students?. This research was classroom action research. Subject of research are the students of program of study history education. The research have two cycles. Every cycle have four phase, i.e: planning, actuating, observation, and reflection. The data collected through interview, observation, and documentation. Data analyses used Milles and Huberman interactive models. From the research, it can be concluded that there are understanding increase of Islamic culture concept. In first cycle, three group of students has opinion of Islamic culture as a culture was characterized by religion (Islam) archeological remains. Meanwhile two groups still seen the concept as a culture who has made by moslem society. In second cycle, five group of students have opinion of Islamic culture as a culture was characterized by Islam archeologicalremains. Secondly, there is more activity of students in teaching learning process which used the models of learning. The students enthusiastic to accompanied every stage of teaching learning process. Based from the findings of research, it can be suggested that: (1) variation of models of learning need to be used in teaching learning process, (2) this research only used in one topic and subject matter, so that it necessary be used in different topic and subject matter for content the similar problem. Key word: Islamic culture, think pair share models of learning